2020
DOI: 10.3389/fphys.2020.00076
|View full text |Cite
|
Sign up to set email alerts
|

Elevated β1-Adrenergic Receptor Autoantibody Levels Increase Atrial Fibrillation Susceptibility by Promoting Atrial Fibrosis

Abstract: Beta 1-adrenergic receptor autoantibodies (β1ARAbs) have been identified as a pathogenic factor in atrial fibrillation (AF), but the underlying pathogenetic mechanism is not well understood. We assessed the hypothesis that elevated β1ARAb levels increase AF susceptibility by promoting atrial fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…Endocardial electrophysiological parameters were measured to evaluate the atrial electrical stability under the β1-AAb stimulation. As reported in our prior work [13], β1-AAb shortened the AERP and stretched the WOV in the rabbits responding to active immunization, which were reversed by blocking β1AR (respectively, P<0.05, Figure 2D,E and Supplementary Figure S2). AF inducibility was significantly elevated in the β1-AAb group under the burst pacing, as well as the AF duration.…”
Section: The β1-aab Decreases the Atrial Electrical Instability And I...supporting
confidence: 83%
See 2 more Smart Citations
“…Endocardial electrophysiological parameters were measured to evaluate the atrial electrical stability under the β1-AAb stimulation. As reported in our prior work [13], β1-AAb shortened the AERP and stretched the WOV in the rabbits responding to active immunization, which were reversed by blocking β1AR (respectively, P<0.05, Figure 2D,E and Supplementary Figure S2). AF inducibility was significantly elevated in the β1-AAb group under the burst pacing, as well as the AF duration.…”
Section: The β1-aab Decreases the Atrial Electrical Instability And I...supporting
confidence: 83%
“…With the developing studies, the higher titers of β1-AAbs are detected in approximately 50% of patients with atrial and ventricular arrhythmias [ 10 , 11 , 12 ]. Our recent work substantiated that elevated β1-AAbs positively correlate with left atrial diameters in paroxysmal AF patients and exacerbate the atrial fibrosis [ 13 ]. Accumulating evidence from basic experiments supported the contributions of β1-AAbs in arrhythmia susceptibilities through promoting numerous adverse cardiac phenotypes, including apoptosis, autophagy, and vulnerable electrophysiologic properties [ 14 , 15 , 16 ].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Transthoracic echocardiography was performed weekly beginning in the first postinfarction week and lasting until the fifth week. Echocardiographic examination was implemented with a Philips HD11XE transthoracic Doppler ultrasound imaging system (Philips Inc., Bothell, WA, USA) as described in our previous work [ 21 ]. The short-axis views of the left ventricle were recorded by two-dimensional M-mode tracing at the level of the papillary muscle.…”
Section: Methodsmentioning
confidence: 99%
“…In adaptive immunity, it has previously been shown that patients with AF have higher levels of autoantibodies, including anti-β1adrenergic receptor (anti-β1-AR) and anti-M2-muscarinic receptor (anti-M2-R) (Yalcin et al, 2015). Anti-M2-R can predict the degree of left atrial fibrosis in pAF patients and β1-AR autoantibody may promote the development of AF by regulating atrial fibrosis (Gurses et al, 2015;Shang et al, 2020). Moreover, the levels of circulating immunoglobulin-free light chains, kappa and lambda, were higher in individuals with AF (Matsumori et al, 2020).…”
Section: Evidence For Immune Remodelingmentioning
confidence: 99%